Comparative Study of Performance of Indian Commercial Banks in the Era of Global Melt-Down - Uppal, R. K. (Journal of Social and Development Sciences, 2011)
The gap regarding the costs and profits is widening among the various bank groups. The present paper is an endeavor to study the comparative costs and profits to study the comparative costs and profits among partially and fully IT-oriented bank groups. The paper concludes that even the costs are high in partially IT-oriented bank groups but their profits are also lesser as compare to fully IT-oriented bank groups and there is significant correlation between operating costs and net profits but insignificant correlation between per employee expenditure and net profits. At the end, paper suggests some areas of comprehensive research.